Effect of Averrhoa carambola L. on the Skin in an Animal Model of Hypertrophic Scarring: Efecto de la Averrhoa carambola L. en la piel en un modelo animal de cicatrización hipertrófica - Córdova-Aguilar, Alberto (2024)
Introduction: Hypertrophic scarring in the skin represents a serious global public health problem, as it physically and emotionally affects people who suffer from it. This makes it necessary to investigate new alternatives for its prevention and treatment. The objective of the study was to compare the effect of Averrhoa carambola L. (star fruit) on the skin under an animal model of hypertrophic healing. Methods: Experimental study; 10 male New Zealand breed rabbits were used, between 3 and 4 months old, with an average weight of 3 to 3.5Kg. The creation of hypertrophic scars in the ears of rabbits was induced under the model described by Morris et al. One of the groups received 1 mL of a 10% aqueous solution of the lyophilized star fruit, while the other received 1 mL of triamcinolone acetate; in both groups the application was intralesional and weekly in a month. After the treatment, under sedation, only the hypertrophic scars were extracted using a biopsy punch and the tissues were preserved in 10% formalin for subsequent pathological examination. Results: The group that received star fruit solution significantly improved the dermis and epidermis in the hypertrophic scars on the ears of rabbits that received treatment. When compared with the group that received triamcinolone acetonide, there were no statistically significant differences. Conclusion: The lyophilized aqueous extract of star fruit at 10% demonstrated a similar effect compare to triamcinolone acetonide (treatment of choice) in reducing the fibrosis of hypertrophic scars in the ears of rabbits. Keywords: Averrhoa carambola L., triamcinolone, hypertrophic scar, animal models. (MeSH/NLM)